Isolation and Characterization of an Endophytic Fungus Colletotrichum coccodes Producing Tyrosol From Houttuynia cordata Thunb. Using ITS2 RNA Secondary Structure and Molecular Docking Study - Talukdar, Rajreepa; Padhi, Srichandan; Rai, Amit K.; Masi, Marco; Evidente, Antonio; Jha, Dhruva Kumar; Cimmino, Alessio; Tayung, Kumananda (Frontiers in Bioengineering and Biotechnology, 2021)
An endophytic fungus isolated from healthy leaf tissues of Houttuynia cordata Thunb., an ethnomedicinal plant of North East India, showed a considerable amount of antimicrobial activity. The ethyl acetate extract of the fungus displayed promising antimicrobial activity against a panel of clinically significant pathogens including Candida albicans, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Bioassay guided purification of the organic extract using column and thin layer chromatography yielded a pure homogenous compound which was identified using spectroscopic methods (essentially by 1H NMR and MS) as tyrosol, a well-known phenylethanoid present in several natural sources. Besides, molecular docking studies against tyrosyl tRNA synthetases (TyrRS) of S. aureus (PDB ID: 1JIL) and E. coli (PDB ID: 1VBM), and CYP45014α-lanosterol demethylase (CYP51) of C. albicans (PDB ID: 5FSA) revealed tyrosol has a strong binding affinity with the enzyme active site residues. The fungus was identified as Colletotrichum sp. and characterized by its genomic ITS rDNA and ITS2 sequences. Phylogenetic analyses showed clustering of our isolate with C. coccodes. Species of Colletotrichum are also reported to be plant pathogens. Therefore, to confirm the endophytic lifestyle of the isolate, ITS2 RNA secondary structure study was undertaken. The result indicated our isolate exhibited differences in the folding pattern as well as in motif structures when compared to those of pathogenic C. coccodes. The findings indicated that endophytic fungi harbouring H. cordata could be explored as a potent source of antimicrobial agents.